Pengembangan Jurnal Digital Berbasis Project Based Learning (PJBL) Dalam Meningkatkan Kesadaran Hukum Dan Prilaku Disiplin Siswa Di SMKN 1 Tegalbuleud Kabupaten Sukabumi - Bayu Bagus Mulyana; Sri Rahayu Pudjiastuti; Mohamad Sutisna (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2025)
This study aims to develop a digital journal based on Project Based Learning (PJBL) as an instructional media in Civics Education (PKn) to enhance students' legal awareness and disciplinary behavior at SMKN 1 Tegalbuleud, Sukabumi Regency. The method employed is Research and Development (R&D) with a simplified Borg & Gall model consisting of five stages: problem identification, data collection, product design, validation, and limited trial. The product was created in both Google Form and interactive PDF formats, featuring project identity sections, activity guidelines, legal values reflection columns, and assessment rubrics. Validation by media and content experts indicated a feasibility score of 87.3% (categorized as highly feasible). A trial involving 30 eleventh-grade students showed an average pretest score of 64.06 and a posttest score of 73.69, indicating an increase of 9.63 points. The Paired Sample t-Test revealed a significant difference (p < 0.05), with an N-Gain of 0.56 (moderate category), suggesting the media's effectiveness. Both students and teachers responded positively, noting ease of use and increased engagement. In conclusion, the PJBL-based digital journal is proven to be effective, feasible, and relevant as a character education tool in Civics learning, particularly in fostering legal awareness and disciplinary behavior among vocational high school students.